Influence of Abiotic Stresses on Morphophysiological Characteristics and Biological Value of Grain Sorghum bicolor (L.) Moench - Oksana Pavlovna Kibalnik; Irina Alexandrovna Sazonova; Yulia Valerievna Bochkareva; Vera Valerievna Bychkova; Dmitry Sergeevich Semin (International Journal of Plant Biology, 2023)
Sorghum is the agricultural crop most adaptable to the effects of abiotic factors, able to tolerate prolonged soil and air droughts, changes in air temperature, insufficient precipitation, salinization, acidification of soils, and many others with the least loss of yield compared to traditional crops such as wheat and barley. However, even among sorghum genotypes, there are samples with varying degrees of resistance to stressors, for example, drought. The aim of this study is a comprehensive study of the influence of abiotic factors on the physiological characteristics and biochemical parameters of sorghum grain. The experiment was carried out on the experimental field and laboratory conditions of the Rossorgo Institute. Drought resistance of plants is determined in the initial phase of development and during the flowering period by the degree of seed swelling in hypertonic solutions and the water regime of the leaves (total water content, water deficiency, moisture loss, and water-holding capacity). The quality of the grain is determined using the spectrophotometry method for the main biochemical components, and likewise, the separation of the protein into fractions. The growing conditions of plants in 2021–2022 differ significantly in terms of hydrothermal indicators. As a result of the conducted research for use in breeding programs for the creation of new varieties and hybrids with increased stress resistance selected samples L-65/14, Magistr has high drought resistance in the degree of seed swelling in hypertonic solutions (55.2–58.9%), which turned out to be at the level of the control variant (61.6–63.7%), and indicators of the water regime of the leaves (total water content of leaf tissues—74.20–77.83%; water-retaining capacity—83.77–85.56%; low moisture loss for 1 h/day—2.86–3.01%). These samples were characterized by the biological value determined by the optimal ratio of major indicators of grain and protein fractions: albumin (16.59–22.75%), globulin (8.13–9.09%), glutelin (9.09–14.01%), and prolamin (5.79–11.50%).